Student Engagement in Project-Based Learning during the Writing Learning Process: A Case Study at State Islamic Senior High School - Nur Ikhsan Amal; I G A Lokita Purnamika Utami; Ni Luh Putu Eka Sulistia Dewi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Student engagement has become one of the most influential factors affecting students’ learning experiences and academic achievement, particularly in English as a Foreign Language (EFL) classrooms. In writing instruction, students frequently encounter challenges related to idea generation, organization, language accuracy, and sustained motivation, making meaningful engagement essential for successful learning. Project-Based Learning (PjBL) has been widely recognized as a student-centered instructional approach that promotes collaboration, authentic learning, and active participation. Although previous research has reported the effectiveness of PjBL in improving students’ writing performance and motivation, limited attention has been given to how students demonstrate behavioral, emotional, and cognitive engagement throughout the writing process, particularly within Indonesian Islamic senior high schools. This research aims to analyze student engagement during the implementation of Project-Based Learning in the writing learning process at State Islamic Senior High School. A qualitative case study design was employed involving eleventh-grade students who participated in project-based writing activities. Data were collected through classroom observations, semi-structured interviews, and documentation and analyzed using the interactive model of Miles, Huberman, and Saldaña (2014). The findings indicate that students demonstrated varying levels of behavioral, emotional, and cognitive engagement during different stages of project implementation. Collaborative learning activities encouraged active participation, increased learning motivation, and promoted deeper cognitive involvement during writing tasks. However, several students experienced challenges related to confidence, idea development, and sustained participation during revision activities. This research highlights the importance of creating collaborative learning environments that support multidimensional engagement throughout the writing process and provides pedagogical implications for English teachers implementing Project-Based Learning in EFL classrooms.